Genetics in thrombophilia - Reitsma, P. H. (Hämostaseologie, 2015)
Venous thromboembolism (VTE) poses a worldwide health burden affecting millions of people each year. The annual incidence of symptomatic VTE, the collective term used here for deep venous thrombosis, pulmonary embolism or both, is 2–3 per thousand inhabitants. The one-year mortality is 20% after a first VTE. Of the surviving patients 15–25% will experience a recurrent episode of VTE in the three years after the first event. Primary and secondary prevention is key to reducing death and disability from VTE. How to make use of our current knowledge of inherited risk of VTE for primary and secondary disease prevention is not straightforward. This despite the fact that in the past two or three decades we have made major strides in enlarging our understanding of inherited VTE risk, and that new inherited risk factors continue to be identified.For primary prevention of VTE genetic testing is not likely to play a role in the future. Genetic variations also determine recurrence risk, albeit that the effect sizes for individual genetic variations are invariably lower than those for first VTE events. Multilocus genetic risk scores improve risk classification, and it is now possible to stratify patients who have had a first venous thrombosis, into subgroups with a high and low risk of recurrence. Whether this approach can be used to tailor intensity and duration of treatment remains to be established.
Keywords: Venous thrombosis; thrombophilia; genetics; mutations